Hubungan Intensitas Nyeri Ibu Post Sectio Caesarea dengan Waktu Inisiasi Menyusui Setelah Rawat Gabung - Putu Eka Deviana Septiari; Ni Nyoman Budiani; Asep Arifin Senjaya; Ni Gusti Kompiang Sriasih (Poltekkes Kemenkes Padang, 2026)
Post-cesarean pain hinders initiation of breastfeeding. A preliminary study at Bali Mandara Hospital showed that the majority of mothers with moderate pain intensity (NRS) only started breastfeeding >4–8 hours postpartum. This study aims to determine the relationship between the intensity of post-cesarean maternal pain and the time of first breastfeeding after the baby was admitted. This study is a non-experimental study with a correlational analytical research type, using a cross-sectional approach. The study was conducted from March to April 2025. A sample of 46 postpartum mothers was taken using a purposive sampling technique. The majority of respondents experienced moderate pain with the time of first breastfeeding mostly at >4-8 hours after the baby was admitted. Univariate analysis is presented in the form of a frequency distribution and bivariate analysis using the Spearman Rank test with the results of p = 0.000, r = 0.782. conclusion : Maternal pain levels following a C-section directly impact the initiation of breastfeeding. To mitigate this, healthcare providers must improve nursing interventions through comprehensive pain management strategies.